أثر التدريب على إعداد الخرائط الذهنية في رفع التحصيل الدراسي وفاعلية الذات الأكاديمية لدى الطلاب المتفوقين عقليا ذوي التفريط التحصيلي بالصف الأول الثانوي - إسماعيل، إبراهيم السيد إبراهيم (جامعة بورسعيد - كلية التربية, 2015)
هدفت الدراسة الحالية معرفة فاعلية تدريب الطلاب المتفوقين عقلياً ذوى التفريط التحصيلى على إعداد الخرائط الذهنية فى رفع تحصيلهم الدراسي وفاعليتهم الذاتية الأكاديمية. وتكونت عينة الدراسة من (24) طالبًا وطالبة موزعين على مجموعتين، الأولى تجريبية مكونة من (12) طالبًا وطالبة تدربوا على إعداد الخرائط الذهنية فى ثلاث مواد دراسية : الفيزياء والجغرافيا والفلسفة، والأخرى ضابطة تكونت من (12) طالباً وطالبة لم يتلقوا تدريبًا على إعداد الخرائط الذهنية. واستخدم الباحث اختبار المصفوفات المتتابعة القياسى لرافن تعريب فؤاد أبو حطب (1977)، ومقياس فاعلية الذات الأكاديمية إعداد الباحث الحالي، ومقياس تقدير الخصائص السلوكية لذوى صعوبات التعلم إعداد فتحي مصطفى الزيات (1999)، وتم الاعتماد على درجات الطلاب فى نتيجتي الشهادة الإعدادية والصف الأول الثانوي كمقياس للتحصيل الدراسي، وباستخدام معادلة مان ويتنى، ومعادلة ولكوكسون، توصلت الدراسة إلى أنه : توجد فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسطات رتب أفراد المجموعة التجريبية والضابطة لصالح التجريبية فى متغيري التحصيل الدراسي وفاعلية الذات الأكاديمية، كما يوجد فرق دال إحصائيًا عند مستوى (0.01) بين متوسطي رتب أفراد المجموعة التجريبية فى القياسين القبلى والبعدى لصالح البعدى فى فاعلية الذات الأكاديمية، بالإضافة إلى أنه لا توجد فروق ذات دلالة إحصائية عند مستوى (0.05) بين متوسطات رتب أفراد المجموعة التجريبية الذكور والإناث فى القياس البعدى لمتغيري التحصيل الدراسي (فى مادتي : الجغرافيا والفلسفة) وفاعلية الذات الأكاديمية، فى حين جاء الفرق دالًا لصالح الذكور فى التحصيل الدراسي لمادة الفيزياء
The current study aims to identify the effectiveness of training the first year secondary gifted under achieving students on preparing mind maps in increasing their academic achievement and their academic self efficacy. The study sample included (24) male and female gifted under achieving students divided into an experimental group (n= 12 students), trained on preparing mind maps (in three study materials : physics, geography and philosophy) , and a control group (n=12 students), not trained on preparing mind maps. The tools used in the study were : Raven’s Standard Progressive Matrices Test (Translated by Foaud Abo- Hatb, 1977), Academic self-efficacy scale (prepared by the current researcher), Behavioral characteristics for students with learning difficulties rating scale (prepared by Fathy Mostafa Elzayat, 1999). Then, the researcher depended on cumulative scores for students in the preparatory and first year secondary schools as an indicator of academic achievement. Using the Mann-Whitney Equation and Wilcoxon Equation, the study reached to: there were significant statistical differences at (α =0.01) between the experimental group and control group in the mean grades of the post academic achievement and academic self-efficacy in favor of experimental group and there were significant statistical difference at (α =0.01) between the mean grade of experimental group in the pre and post academic self-efficacy in favor of the post measurement, Whereas there were no significant statistical differences at (α =0.05) between the mean grades of experimental group male and female in the gain of the two variables of academic achievement (in geography and philosophy) and academic self-efficacy ,but there were significant statistical difference in favor of male students in academic achievement of physics
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- التحصيل الأكاديمي -- الطلاب المتفوقين عقليا ذوي التفريط التحصيلي -- مصر